Varieties of Capitalism in Southeast Asia - Moore, Joel David (The Political Economy of East Asia, 2018)
This book explains the political origins and evolution of capitalist institutions in developing countries by looking at distinct patterns in the electronics industry in three Southeast Asian countries: Thailand, Malaysia, and Singapore. An analysis of the political determinants of these patterns has a number of theoretical and practical implications. It includes a new explanation for family business behavior, a unified framework for explaining capitalist varieties, a guide for institutional reform, and a comparative examination of three dynamic Asian economies that provides important insights to students, scholars, and people in business. .